Mutation affecting the houskeeping (low affinity) phosphate permease of Neurospora crassa - R L Metzenberg (Fungal Genetics Reports, 1999)
No mutation affecting the structure or expression of the housekeeping (low affinity) phosphate permease of Neurospora crassa has been reported. The null double mutant lacking both high affinity repressible permeases cannot grow at low phosphate concentrations and high pH. A presumptive mutant affecting the housekeeping permease has been isolated as a suppressor of the double mutant's inability to grow under the restrictive condition.